Economic Estimation of Investment Project Efficiency in Complex Development of Industrial Territory - A. P. Zelisko (Вестник Российского экономического университета имени Г. В. Плеханова, 2025)
Annual growth in modeling market of town-planning causes the emergence of new solutions for different stages of life cycle of construction projects. The author studied factors influencing the development of modeling technologies in this sphere by factor, cluster and disperse analysis. Factor analysis means thorough researching on how different factors influence the final figure that is presented in the research by building companies in the world and in Russia. Cluster analysis is a multi-dimensional statistic procedure that collects information about projects and adjusts them in relatively similar groups. Discriminant analysis is a method of statistic analysis used to resolve tasks of dividing data into groups. It can find differences between groups and classify projects by the principle of max similarity. The method implies the presence of two or more groups different from each other by certain variables, which can be measured on interval scale.